La "Reforma Liberal” en Honduras y la hipótesis de la “Oligarquía Ausente": 1870-1930 - Euraque, Darío A. (1991)
In this contribution to a key period of the history of Central America, the author discusses the Liberal State in Honduras and major aspects of the Honduran economy from 1870 to 1930. Subsequently, he addresses the question of whether or not a “Honduran oligarchy” developed during that period.